Age of Natural Menopause Among Jordanian Women and Factors Related to Premature and Early Menopause - Bustami M; Matalka KZ; Elyyan Y; Hussein N; Hussein N; Abu Safieh N; Thekrallah F; Mallah E; Abu-Qatouseh L; Arafat T (Dove Medical Press, 2021)
Mona Bustami,1 Khalid Z Matalka,2 Yousef Elyyan,3 Nagham Hussein,4 Nour Hussein,5 Nayef Abu Safieh,5 Fida Thekrallah,3 Eyad Mallah,6 Luay Abu-Qatouseh,1 Tawfiq Arafat7 1Department of Pharmacology and Biomedical Sciences, Faculty of Pharmacy and Medical Sciences, University of Petra, Amman 11196, Jordan; 2Matalka’s Scientific Writing, Lexington, MA, USA; 3Department of Obstetrics and Gynecology, Jordan University Hospital, Amman, Jordan; 4Istishari Hospital, Amman, Jordan; 5School of Medicine, University of Jordan, Amman, Jordan; 6Department of Pharmaceutical Medicinal Chemistry and Pharmacognosy, Faculty of Pharmacy and Medical Sciences, University of Petra, Amman 11196, Jordan; 7Jordan Center for Pharmaceutical Research, Amman, JordanCorrespondence: Mona Bustami Email mbustami@uop.edu.joObjective: The aim of this study was to assess factors related to the onset of premature/early natural menopause among Jordanian women.Methods: A cross-sectional study was conducted in early 2016. Subjects were enrolled based on random drop-off technique to the Obstetrics and Gynecology clinics at the Jordan University Hospital. Women 18 years of age and above were initially eligible to enroll, and women who had surgically induced menopause or specific disease were excluded from the analysis. Relevant data were collected using a questionnaire that included 30 questions. The following variables were collected: socio-demographic, body mass index, chronic conditions, diseases, reproductive characteristics, and health status. Hormone indicators of menopause were tested by measuring estrogen (E2) and follicle-stimulating hormone (FSH) levels. Age at natural menopause (ANM) was self-reported retrospectively and considered an independent variable against BMI, smoking, hormone therapy, and concomitant diseases. Association analysis and multinomial logistic regression were used to examine the associated factors of ANM with adjusted odds ratios (ORs), and their 95% confidence intervals (CIs) were reported.Results: A total of 409 women were included in the analysis, aged between 20− 75 years. The mean ANM in our sample was 48.5± 5.0, with 2.7% of the women experienced premature menopause (ANM < 40) and 7.8% early menopause (ANM 40– 44). Within the menopause women (n=242), the percentage of women who had premature menopause was 4.5%, 13.6% with early menopause, and 21.1% with late menopause (ANM > 52). Smoking was the major risk factor for premature/early menopausal age among Jordanian women with an OR of 2.46 (95% CI: 1.08– 5.59, p< 0.05). On the other hand, women with occasional arthritis symptoms and diseases such as hypertension, diabetes, dyslipidemia, and their combination were associated with average (45– 52 years) or late menopause (> 52 years).Conclusion: Smoking is the main contributor of premature/early menopause in Jordanian women. Increased awareness and public health policy about the adverse effects of smoking on women’s reproductive health are needed.Keywords: Jordanian women, menopause age, smoking, diseases, socioeconomic variables